Educational Management Based on Local Wisdom - Muhamad Sholeh (Universal Journal, 2020)
Local wisdom-based education or local excellence is education that utilizes local and global excellence in the aspects of economics, arts and culture, human resources, language, information and communication technology, ecology, and others into the school curriculum which ultimately benefits the development of competency of learners can be used for global competition. Local wisdom is a term for local ideas. However, it must be remembered, the idea in question must be of a full wisdom according to its name, wise, of good value, and firmly planted across generations in society. As the name implies, the core value of local wisdom itself is local. Thus, local wisdom can only apply in a community that embeds it.